Facing the Drilling and Blasting Difficulties at Helwan Quarry, Egypt - M. Khaled; K. Abdel Rahman; M. Khattab (International Society of Explosives Engineers, 2008)
Helwan limestone quarry is located at a distance of 35 km (21.7 miles) to the south of Cairo downtown. Drilling and blasting operations are used to extract the limestone for the Helwan Cement Company (HCC). In 1980’s a new urban community was constructed adjacent to the quarry. This situation led to shifting of the old quarry 5.0 km (3.1 miles) to its current location, to avoid causing blasting problems to the new community. Unfortunately, the new quarry is opened in a highly faulted area, with weak zones of brittle materials. The drilling and blasting crew is facing many difficulties due to the geological complexity along these zones. Moreover, the extension of this community towards the new quarry makes the control of ground vibrations is very important.